Вибір технічних параметрів і схемо-технічних рішень системи захисту від несанкціонованого запису звукозаписними пристроями - Олейніков, А. М.; Білоцерківець, О. Г. (My University, 2021)
When developing a system of protection against unauthorized recording by sound recording devices, there is a need to choose a microcontroller that meets the requirements for performance, reliability, application conditions, etc. The main goal is to choose a microcontroller with a minimum price (to reduce the total cost of the system), but at the same time meets the system specifications, ie the requirements for performance, reliability, application conditions.
Keywords: Система зихисту; мікроконтролер; ATmega328